2022
DOI: 10.1186/s12905-022-01783-1
|View full text |Cite
|
Sign up to set email alerts
|

Perceived social support and coping style as mediators between resilience and health-related quality of life in women newly diagnosed with breast cancer: a cross-sectional study

Abstract: Background Breast cancer may impair health-related quality of life (HRQoL). We examined the mediating roles of perceived social support (PSS) and coping style (CS) in the relationship between resilience and HRQoL in newly diagnosed breast cancer patients. Methods Following a cross-sectional design, 431 patients completed a survey at two hospitals in Shaanxi Province, China. Four validated self-report measures assessed HRQoL, psychological resilienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 44 publications
(40 reference statements)
4
9
0
1
Order By: Relevance
“…Our correlation results show that quality of life of nurses in IDDs was positively correlated with social support and its various dimensions. The higher the social support, the higher the quality of life, which is consistent with the existing relevant research results (Iwanowicz‐Palus et al, 2021 ; Zhou et al, 2022 ). Nurses' quality of life may improve if they can obtain sufficient material support in their work and life, as well as good social relationships with others.…”
Section: Discussionsupporting
confidence: 91%
“…Our correlation results show that quality of life of nurses in IDDs was positively correlated with social support and its various dimensions. The higher the social support, the higher the quality of life, which is consistent with the existing relevant research results (Iwanowicz‐Palus et al, 2021 ; Zhou et al, 2022 ). Nurses' quality of life may improve if they can obtain sufficient material support in their work and life, as well as good social relationships with others.…”
Section: Discussionsupporting
confidence: 91%
“…This result was in accordance with prior studies on associations among psychological factors, coping strategies, and QoL. For instance, Zhou et al 23 reported the mediating role of resignation between resilience and QoL among patients with breast cancer. Another study confirmed that resignation was an important mediating factor between illness uncertainty and mental QoL.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our study, previous studies demonstrated a negative association between resignation and QoL among patients with chronic lymphedema and breast cancer. 23 , 31 As expected, our study revealed that resignation partially mediated the relationship between self-efficacy and QoL. In other words, higher self-efficacy can reduce patients’ use of resignation coping when facing CHB-related stress and accordingly improve their QoL.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations